Pengaruh Tingkat Pendidikan, Sosialisasi dan Pemahaman Akuntansi Terhadap Penyusunan Laporan Keuangan UMKM Berdasarkan SAK EMKM: Studi Kasus Kecamatan Mulyorejo - Prastia Citra Ningati; Ulfa Puspa Wanti Widodo (Economic Reviews Journal, 2024)
Micro, Small and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy by contributing to job creation, improving living standards and more equal distribution of income. However, many MSMEs experience difficulties in preparing financial reports that comply with the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). This difficulty is often caused by limited accounting knowledge, the complexity of accounting standards, and the view that financial reports are not essential. This research emphasizes the importance of education, socialization and understanding of accounting to improve the quality of MSME financial reporting. Both formal and non-formal education, such as outreach and training, can help MSME owners manage financial information better. By using descriptive statistical methods and cross-sectional survey data from MSMEs in Mulyorejo District, Surabaya, the results of this research show that education, socialization and understanding of accounting have a positive impact on the preparation of financial reports based on SAK EMKM. Therefore, steps to improve the quality of MSME financial reports through education, training and outreach need to continue to be encouraged.